ESTIMATING THE IMPACT OF ADVANCE CARE PLANNING ON HOSPITAL ADMISSIONS, OCCUPIED BED DAYS, AND ACUTE CARE SAVINGS. Issue 2 (1st June 2013) - Hunt, R W; Jones, L; Owen, L; Seal, M
Abstract : Background: Apart from the ethical imperatives and improved client outcomes in support of advance care planning, a compelling argument for health care administrators is the containment of escalating health care costs in ageing communities. Advance care planning activity has repeatedly been shown to reduce hospital admissions. 1–3 In particular, care toward the end of life is expensive, and advance care planning reduces the use of invasive and expensive hospital treatments during terminal illness. Aim: To estimate the impact of advance care planning activity on the number of hospital admissions, occupied bed days, and hospital costs in Adelaide, South Australia. Methods: We apply the results of previous research on the impact of advance care planning, 1–3 to the number of advance care plans made following implementation of the Respecting Patient Choices (RPC) Program in community and hospital settings in Adelaide, to estimate the number of saved hospital admissions, occupied bed days, and costs. Results: Data records began in 2005 during The Queen Elizabeth Hospital RPC pilot. Data collection from community settings began in 2008, and then from other public hospitals in the Central and Northern Adelaide metropolitan area from 2010. A total of 2604 advance care plans were made and the estimated Occupied Bed Days saved was 23 957. The number of admissions to hospitals from the 42 Nursing Homes engaged in advance care planning was estimated to be reduced by 840 over the last 2–3 years. Discussion: Several assumptions are used in applying previous research to calculate the estimated hospital savings. The estimates suggest significant savings, which should be of interest to health administrators. Costs and savings will be detailed in the presentation. Further investment and evaluation of the impact of advance care planning is clearly warranted. Conclusion: A relative small investment in advance care planning has the potential to reap considerable savings in hospital use, particularly at the end of life.